Crystal structure of 2-aminopyridinium 6-chloronicotinate - Jeeva Jasmine, N.; Rajam, A.; Thomas Muthiah, P.; Stanley, N.; Abdul Razak, I.; Mustaqim Rosli, M. (International Union of Crystallography, 2015)
In the title salt, C5H7N+C6H3ClNO, the 2-aminopyridinium cation interacts with the carboxylate group of the 6-chloronicotinate anion through a pair of independent N—H O hydrogen bonds, forming an R2 2(8) ring motif. In the crystal, these dimeric units are connected further via N—H O hydrogen bonds, forming chains along [001]. In addition, weak C—H N and C—H O hydrogen bonds, together with weak – interactions, with centroid–centroid distances of 3.6560 (5) and 3.6295 (5) A ° , connect the chains, forming a twodimensional network parallel to (100).